The Effect of Motivation on the Needs of EAP and EOP for Undergraduate Students: The Case of Universitas Pancasila - Said, Mashadi; Meidasari, Venny Eka; Iswadi (Advances in Social Sciences Research Journal, 2022)
This study aims at describing the effects of integrative motivation on the needs of English for Academic Purposes (EAP) and English for Occupational Purposes (EOP) of the students of Universitas Pancasila. The study employed the survey method using multiple regression and correlation analysis. The population of the study consisted of 12708 students of Universitas Pancasila. Of that number, 388 counted with the Slovin formula at the significance level of 5% participated in the study. A random sampling method was employed to collect the sample. Data were collected with questionnaires with the 1-6 Likert scale. Data were then analyzed with product moment analysis, multiple regression, F test, and T-test with an alpha of 5%. The writers employed the Version 22 SPSS program. The results of the study indicate (1) the absence of the effect of integrative motivation on the needs of EAP and EOP for the students of Universitas Pancasila, (2) the presence of the effect of instrumental motivation on the needs of EAP and EOP for the students of Universitas Pancasila, and (3) the presence of the joint effect of integrative motivation and instrumental motivation on the needs of EAP and EOP. The needs are closely correlated with integrative motivation and instrumental motivation. The results of the study indicate the improvement of the EAP and EOP curricula for undergraduate students of Universitas Pancasila in particular and all Indonesian higher educations in general.